The Flour Source’s Role as a Fermentation Substrate Influences the Physical Attributes of Nata de Coco - Arjunaatha Tyaga Naryamajati; Laeli Fatikhatur Rohmah; Anisa Agustina Vivianti; Dewangga Priyo Sasmito; Vishal Chhetri; Alwani Hamad (Research in Chemical Engineering, 2024)
The production of coconut water in Indonesia is very abundant, but there are problems with its utilization. Discarding unused coconut water often results in an unpleasant odor, as fermentation produces acetic acid pollution. Coconut water has an economic value and is rich in nutrients. One product that can be made from coconut water is nata via fermentation. Making nata requires a source of carbon that can be obtained from flour and is influenced by its type. Thus, this study aims to examine the effect of adding different types of flour as a source of carbon for fermentation in making nata de coco. We use corn, tapioca, rice, and modified cassava flour (mocaf), along with granulated sugar as a sample control. The resulting nata de coco is analyzed for its physical characteristics, including yield, moisture content, and nata thickness. The results showed that nata made using carbon sources from rice flour produced the greatest yield (69.55%), as well as the highest thickness (3.958 mm). Nata, derived from rice flour, also has the highest moisture content (>85%). The study's results indicate that the selection of flour as a carbon source during nata de coco production significantly impacts its yield, thickness, and moisture content